Effect of Welding Speed on Tool Pin Profile using Friction Stir Welding - Syed Rabbani Bash, Dr.G.Thirupati Reddy, (International Journal of Scientific Research and Management (IJSRM), 2015)
Abstract Friction stir welding (FSW) process is an emerging solid state joining. The FSW process parameters such as rotational speed, welding speed, axial force and attack angle play vital roles in the analysis of weld quality. In this investigation an attempt has been made to understand the influences of welding speed and pin profile of the tool on friction stir processed (FSP) zone formation in AA2014 aluminum alloy. The most suitable method for welding AA 2014T6 is solid state joining process. Friction stir welding (FSW) is an emerging solid state joining process which avoids bulk melting of the basic material, hot cracking and porosity. Tri-flutes and taper screw thread pin curvature have been used to fabricate the joints. Mechanical properties of AA 2014-T6 weldments will be evaluated at the weld center of all the joints. From the results it is observed that joints at 40mm/min fabricated by taper cylindrical threaded Triflute pin and taper cylindrical pin profile give better mechanical properties than joints fabricated at 50mm/min. In fact the addition of a transition geometry structure, proper flow, mixing and forging of the plasticized work piece material that flows from the front of the probe as the probe moves in welding direction, due to these mechanical properties of the weld specimen increased.